Caerin 1.1 and 1.9 inhibit glioblastoma growth associated with modulation of the ARHGAP26-β-catenin axis and enhancing intratumoral CD8+ T cell infiltration - Furong Zhong; Jinyi Wu; Hongyin Wu; Yichen Wang; Fengyun Xiao; Bin Xu; Junjie Li; Yuandong Luo; Quanlan Fu; Xiaosong Liu; Tianfang Wang; Guoying Ni; et al. (PLoS ONE, 2026)
Glioblastoma (GBM) is an aggressive brain tumor with limited effective treatment options and poor patient outcomes. This study investigates the antitumor activity and underlying mechanisms of of host defense peptides caerin 1.1 (F1) and caerin 1.9 (F3) in glioblastoma models. F1/F3 treatment inhibited the proliferation of U87 cells and was associated with increased expression of ARHGAP26, suppression of β-catenin signaling pathway, and reduced the expression of downstream targets including MMP2, MMP7, and VEGFA. Cell death is primarily induced through apoptosis-related pathways, while pyroptosis-related and PI3K-related signaling showed more limited alterations. Notably, in immunodeficient NSG mice, F1/F3 altered the tumor immune microenvironment by promoting macrophage infiltration and M1-like polarization but did not significantly inhibit tumor growth. In contrast, in PBMC-humanized NSG mice, F1/F3 significantly suppressed U87 tumor growth and was associated with increased infiltration of macrophages and CD8 + T cells, together with reduced PD-L1 expression. These findings demonstrate that F1/F3 exerts both direct anti-tumor effects and immune-modulatory activities in glioblastoma models. The results support further investigation of caerin peptides as potential immunomodulatory therapeutics for glioblastoma.